Plan de negocio para una empresa comercializadora de productos y artículos de limpieza y su incidencia en el mercado del cantón Durán, año 2015. - Amagua Yela, Silvana María (2015)
This business plan it developed to meet the needs of the inhabitants of the canton Durán by a marketer of products and cleaning supplies with wholesale and retail, targeting a housewife and local companies. A market study was conducted through a survey where it was found that the products and cleaning supplies have a high percentage of unsatisfied demand, and the absence of a marketer of products and items cleanliness has led to find products of poor quality, high prices and little variety. The technical study determined the requirements for the design and operation of the project and the location, right size and capacity of the marketer to meet unmet demand. In the economic study - financial feasibility of this project is shown with an initial investment of $ 30.965,83 to launch the business. The project is attractive by financial indicators, an internal rate of return of 12.81% per annum, this being the maximum rate that can support a project financing, a net present value of $ 2,849.46 over the life of the project and a Profit rate - cost of 1.28 indicating that for every dollar invested in the marketing, has $ 0.28 of income. With these results we can conclude that the business plan is viable and profitable, because there is acceptance of the population and the indicators show positive results for investment. Effective marketing strategy arises to reach consumers and make known the products of a new marketer of cleaning.